Quantitative microstructural analysis of mylonites formed during Alpine tectonics in the western Mediterranean realm. (February 2020) - Ortolano, Gaetano; Fazio, Eugenio; Visalli, Roberto; Alsop, G. Ian; Pagano, Mario; Cirrincione, Rosolino
Abstract: Quantitative microstructural investigations involving new GIS-based tools are applied to three different types of mylonitic rocks. These techniques enable mineral shape distribution maps to be produced, thereby allowing the nature and relative percentage of the weakening vs. hardening layers, as well as their kinematics, to be obtained within a statistically meaningful dataset. Selected rock-types are derived from shearing associated with the meso-Alpine strike-slip tectonics of the western Mediterranean realm, which since the Paleocene has involved, skarn, migmatitic paragneiss and tonalites. These rocks belong to a deep-seated portion of the original southern European Variscan chain known as the Calabrian Pelortani Orogen. Microstructural maps reveal porphyroclastic domains, represented alternatively by feldspar, amphibole, pyroxene or scapolite, that can be distinguished from weakening phase areas, characterised by quartz, biotite plus quartz, or alternatively by calcite when the weakening layer is controlled predominantly by skarns. Image elaboration of porphyroclastic domains was employed to estimate the dominant shear-type, with Rigid Grain Analysis, indicating a pure shear component of 66–68% for the mylonitic tonalites; 62–66% for the mylonitic paragneisses; and 58–62% for the mylonitic skarn. Grain boundary mapping of the quartz-rich domains also permits an estimate of shear strain rate, which ranges from 1.14*10 −12 (1/s) for mylonitic paragneiss to 5.91*10 −12 (1/s), for mylonitic tonalite, and is in accord with high strain zones in natural settings. Finally, our results opened up new perspectives in the interpretation of the kinematics and rheology of this exhumed sector of the southern European Variscan chain reflecting the deep-seated meso-Alpine strike-slip tectonics of the western Mediterranean realm. Highlights: New ArcGIS® toolbox performing grain size distribution parameters subdivided per mineral types. Automated extraction of fabric parameters from high-resolution thin section scans combined with classified μ-XRF maps. Rigid Grain Net analysis for extraction of sub-simple shear percentage. Quartz paleopiezometry and strain rate estimates.